Mapeamento genético de marcadores SNPs (Single Nucleotide Polymorphisms) em cana-de-açúcar (Saccharum spp.) - Jardim, Priscila Magalhães da Veiga (2018)
Sugarcane is an important culture quite relevant to the Brazilian economy. The production is growing as well as a cultivated area is increasing every year. The genome of this culture is still deficient due to complications such as high ploidy and the big genome that presents. Among the different genetic characterization studies, the development of genetic maps is important for providing information about the genome structure of a species. In addition, it can help develop the techniques of interpretation and use of genetic information. They provide more understanding of how genetic information is organized in the genome of sugarcane supplying a lack in the basic element in this culture. The maps constructed for sugarcane, so far, not shown saturated. This work was obtained a map for sugarcane using SNP markers based on genotyping-by-sequencing technology in next-generation sequencing using the target sequencing strategy (RAPiD-Seq). For obtaining the map, 103 clones RB97327 and RB72454 were used. Probes were designed based on sequence similarity using the sorghum genome as a reference. The construction of the binding groups, considering as a binding criterion of a recombination fraction equal 0.20; allowed the identification of 249 binding groups for the biparental population with 1: 1 segregation. A total of 20555 polymorphic were scored in the analysis. The sum of the average sizes of homeologia groups identified, using the sorghum genome as a reference, was 3964.68 cM for the female parent and 3797.05 cM for the male parent.